Moxifloxacin-induced acute psychosis: A case report with literature review - Faizan Mazhar; Shahzad Akram; Nafis Haider (Wolters Kluwer Medknow Publications, 2016)
Third generation quinolones are extensively used to treat a variety of common bacterial infections. Due to their extensive use in clinical practice, an increase in neuropsychiatric events has been reported. We report the case of psychotic symptoms occurs after three doses of moxifloxacin in a healthy adult male with no underlying risk factors. After the discontinuation of moxifloxacin treatment, there was a complete resolution of patient's symptoms. The case draws attention to a rare side effect of a commonly use drug and alert the clinicians to be cautious in those patients that have a baseline risk factors which makes the patient more susceptible to such adverse drug effect.